Implementation of Madhava Creative Startup Digital Public Relations Activities in Shaping Brand Image in Balinese Society - Sarah Bella Ahrens; Christine Julyana Siagian; Muthia Zulfa Amanda (Jurnal Indonesia Sosial Teknologi, 2024)
COVID-19 is a virus that spreads throughout Indonesia and creates various obstacles in today's business world. In this study, the author discusses the implementation of public relations activities for the creative startup Madhava in shaping the brand image in Balinese society. The purpose of this study was to determine the digital advertising activities of the creative startup Madhava in shaping the brand image in Balinese society. The theory used is the elaboration likelihood theory. This theory is used in this study because it deals with the ways in which people are expected to process persuasive messages given by companies. The elaboration likelihood theory theory is supported by digital advertising activities, namely publicity and events to find out digital advertising activities carried out by the management of Madhava creative startups in shaping brand image in Balinese society.